Profiles of adversity and resilience resources: A latent class analysis of two samples - Lines, Robin; Crane, M.; Ducker, Kagan; Ntoumanis, Nikos; Thogersen-Ntoumani, Cecilie.; Fletcher, D.; Gucciardi, Daniel (2019)
© 2019 The British Psychological Society Adversities refer to events that are characterized by perceived or actual threat to human functioning. Often considered deleterious for health and well-being, recent work supports an alternative picture of the effects of adversity on human functioning, such that a moderate amount of adversity – when compared with none or high levels – can be beneficial. We extend this body of work in the current study by considering the breadth or type of adversities experienced simultaneously (referred to as polyadversity), with a focus on individual profiles of lifetime adversities. Latent class analysis was employed to explore different configurations of lifetime adversity experiences in two independent samples and examine how these latent classes differed with regard to resilience resources (i.e., optimism, hope, self-efficacy, and bounce-back ability). University students (N = 348) and members from the broader community (N = 1,506) completed measures of lifetime adversity exposure and resilience resources. Three polyadversity classes were revealed in each sample, with both producing a high and a low polyadversity class. The third class differed between samples; in the student sample, this class represented experiences of vicarious adversity, whereas in the community sample, it represented moderate levels of exposure to adversity. Support for the adaptive nature of a moderate amount of adversity exposure was found in the community sample but not in the student sample. This study produces initial evidence of how lifetime adversity experiences group together and how class membership is related to resilience resources.